Comparison of Two Amplification Technologies for Detection and Quantitation of Human Immunodeficiency Virus Type 1 RNA in the Female Genital Tract - Bremer, James (American Society for Microbiology, 2000)
Human immunodeficiency virus type 1 (HIV-1) RNA levels in female genital tract and peripheral blood samples were compared using two commercial amplification technologies: the Roche AMPLICOR HIV-1 MONITOR test and either the Organon Teknika nucleic acid sequence-based amplification (NASBA-QT) assay or the NucliSens assay. Estimates of HIV-1 RNA copy number were derived from internal kit standards and analyzed unadjusted and adjusted to a common set of external standards. We found a discordance rate of approximately 18% between the two technologies for the detection of HIV-1 in either the genital tract or peripheral blood samples. Detection discordance was not consistent among specimens or among women. There were no significant differences in adjusted or unadjusted estimates of HIV-1 RNA copy number in the genital tract samples using the AMPLICOR HIV-1 MONITOR test and either the NASBA-QT assay or the NucliSens assay. In addition, the estimated HIV-1 RNA copy number in peripheral blood samples did not differ when tested with the NucliSens assay and the AMPLICOR HIV-1 MONITOR test using kit standards. However, there was a significant difference in estimated RNA copy number between the NASBA-QT assay and the AMPLICOR HIV-1 MONITOR test for internal kit standards, which, as we have previously shown, was eliminated after adjustment with the external standards. Our results suggest that the Roche and Organon Teknika assays are equivalent for quantifying HIV-1 RNA in female genital tract specimens, although variation in detection does exist.